Development of chimeric and bifunctional antagonists for CLR/RAMP receptors - Chang, Chia Lin (PLoS One, 2019)
CGRP, adrenomedullin (ADM), and adrenomedullin 2 (ADM2) family peptides are important neuropeptides and hormones for the regulation of neurotransmission, vasotone, cardiovascular morphogenesis, vascular integrity, and feto‒placental development. These peptides signal through CLR/RAMP1, 2 and 3 receptor complexes. CLR/RAMP1, or CGRP receptor, antagonists have been developed for the treatment of migraine headache and osteoarthritis pain; whereas CLR/RAMP2, or ADM receptor, antagonists are being developed for the treatment of tumor growth/metastasis. Based on the finding that an acylated chimeric ADM/ADM2 analog potently stimulates CLR/RAMP1 and 2 signaling, we hypothesized that the binding domain of this analog could have potent inhibitory activity on CLR/RAMP receptors. Consistent with this hypothesis, we showed that acylated truncated ADM/ADM2 analogs of 27–31 residues exhibit potent antagonistic activity toward CLR/RAMP1 and 2. On the other hand, nonacylated analogs have minimal activity. Further truncation at the junctional region of these chimeric analogs led to the generation of CLR/RAMP1-selective antagonists. A 17-amino-acid analog (Antagonist 2–4) showed 100-fold selectivity for CLR/RAMP1 and was >100-fold more potent than the classic CGRP receptor antagonist CGRP8-37. In addition, we showed (1) a lysine residue in the Antagonist 2–4 is important for enhancing the antagonistic activity, (2) an analog consisted of an ADM sequence motif and a 12-amino-acid binding domain of CGRP exhibits potent CLR/RAMP1-inhibitory activity, and (3) a chimeric analog consisted of a somatostatin analog and an ADM antagonist exhibits dual activities on somatostatin and CLR/RAMP receptors. Because the blockage of CLR/RAMP signaling prevents migraine pain and suppresses tumor growth/metastasis, further studies of these analogs, which presumably have better access to the tumor microenvironment and nerve endings at the trigeminal ganglion and synovial joints as compared to antibody-based therapies, may lead to the development of better anti-CGRP therapy and alternative antiangiogenesis therapy. Likewise, the use of bifunctional somatostatin-ADM antagonist analogs could be a promising strategy for the treatment of high-grade neuroendocrine tumors by targeting an antiangiogenesis agent to the neuroendocrine tumor microenvironment.